Protective role of autophagy in branched polyethylenimine (25K)- and poly(L-lysine) (30–70K)-induced cell death - Lin, Chia-Wei; Jan, Ming-Shiou; Kuo, Jung-Hua Steven; Hsu, Li-Jin; Lin, Yee-Shin (European journal of pharmaceutical sciences, 2012)
Polyethylenimine (PEI) and poly(L-lysine) (PLL), which are cationic polymers used for gene therapy, are known to be cytotoxic, but their molecular mechanisms of cell death are not fully understood. In this study, we provide evidence that PEI and PLL induced autophagy in HeLa cervical cancer cells. In cells overexpressed with green fluorescent protein (GFP)-microtubule-associated protein 1 light chain 3 (LC3) fusion protein, PEI and PLL induced fluorescent puncta formations that represent LC3 recruitment to autophagosomes. In Western blot analysis, conversions of the LC3-I to LC3-II were significant, and p62 degradation was observed in cells treated with PEI and PLL. At higher doses, the ability of endosomal escape by PEI facilitates the conversion of LC3-I to LC3-II without the use of lysosomal protease inhibitors. From the analysis of annexin V-flourescein isothiocyanate (FITC) and propidium iodide (PI) staining by flow cytometry, both apoptosis and necrosis occurred in PEI- and PLL-treated cells. Significant activated caspase-3 expression was detected in PLL- and PEI-treated cells. By applying Z-VAD apoptotic inhibition, apoptosis and autophagy may occur independently or autophagy may be in the upstream of apoptosis on PEI- and PLL-treated cells. The degree of cell death was higher in incubated HeLa cells treated with PEI or PLL plus autophagy inhibitors (3-methyladenine (3-MA) and wortmannin). Treatment with these autophagy inhibitors, however, did not inhibit LC3-II formation specifically. In addition, PEI and PLL induced higher degree of cell death in atg5−/− mouse embryonic fibroblast (MEF) cells than in wild-type cells. Autophagy was also induced in PEI- and PLL-treated MEFs, as evidenced by the formation of LC3-II in wild-type-but not in atg5−/− MEFs. These results indicate that PEI and PLL can trigger both death and survival pathways simultaneously, and autophagy played a role in cell survival in PEI- and PLL-treated cells. Our study therefore provides deeper insight into the molecular mechanisms of cell death caused by cationic polymers.